THE IMPACT OF TECHNOLOGY INTEGRATION ON TOEFL PERFORMANCE: ONLINE PLATFORMS AND LANGUAGE APPS AT UNIVERSITAS MUHAMMADIYAH ACEH - Farsia, Lina; Sarair, Sarair (Jurnal Dedikasi Pendidikan, 2025)
This study investigates the use of technology by students at Universitas Muhammadiyah Aceh in their preparation for the TOEFL exam. A quantitative descriptive approach was employed, with data collected through a structured questionnaire. The findings reveal that 90% of respondents regularly utilize technology, particularly smartphones and laptops, alongside online platforms such as YouTube, Magoosh, and Duolingo. These tools were found to be effective in providing access to study materials and practice tests, with students emphasizing their convenience and accessibility. Additionally, students reported positive impacts on their English language learning, citing increased motivation, improved time management, and greater confidence in their TOEFL preparation. The study highlights the significant role of technology in enhancing learning efficiency and recommends that educational institutions further integrate technological tools to support students in standardized test preparation